Digital Transformation in the Indonesian Banking Industry: A Qualitative SWOT Analysis of Mobile Banking Initiatives in Conventional Financial Institutions - Ula, Vita Rokhimatul (Generate Digital Publishing, 2025)
Objective: This study aims to analyze the internal and external factors that influence the development of mobile banking in conventional banks in indonesia, as well as formulate sustainable strategies that are able to maximize opportunities and overcome challenges in the era of digital transformation. Research Design & Methods: The study used a descriptive qualitative approach with SWOT analysis method to identify the strengths, weaknesses, opportunities, and threats faced by conventional banks in the implementation of mobile banking. Data was obtained through the study of current literature, industry reports, and relevant academic publications. Findings: The analysis shows that reputation, credibility, and customer loyalty are key strengths that can be leveraged to overcome cost constraints, IT infrastructure complexity, and internal resistance to new technologies. Strategic opportunities include expanding financial inclusion in remote areas and improving operational efficiency through automation and analytics technology. Key threats include the digital divide and increased cybersecurity risks. Implications & Recommendations: Conventional banks should adopt a mobile banking development strategy that emphasizes cross-stakeholder collaboration, relevant product innovation, and digital literacy programs to reduce the access gap. In addition, investment in cybersecurity and IT infrastructure modernization should be prioritized to maintain customer trust. Contribution & Value Added: This research provides a practical contribution in formulating a sustainable mobile banking strategy in Indonesia by considering local conditions, digital divide, and market dynamics. Academically, this research enriches the literature on the application of SWOT analysis to the development of digital financial services in developing countries.